Transition metal (Fe, Co, Ni, and Mn) oxides for oxygen reduction and evolution bifunctional catalysts in alkaline media - Osgood, Hannah; Devaguptapu, Surya V.; Xu, Hui; Cho, Jaephil; Wu, Gang (Nano today, 2016)
[Display omitted] •Review transition metal oxide catalyst for electrochemical energy and conversion via O2 electrocatalysis.•Provide an overview for cobalt, manganese, nickel, and iron oxide catalysts in terms of their synthesis, structure/morphology, and catalytic activity.•Focus on elucidation of synthesis–structure–activity correlations for metal oxide nanocomposite catalysts.•Discuss future oxide catalyst approaches to addressing challenges for ORR and OER catalysis. In recent years, a large amount of focus has been given to the development of alternative energy sources that are clean and efficient; among these, electrochemical energy holds potential for its compatibility with solar and wind energy, as well as their applications in fuel cells, and metal-air batteries, and water electrolyzers. However, these technologies require the use of highly active and stable catalysts to make these applications feasible. Current catalysts consist of precious metals such as platinum and iridium, which are expensive and block common access to electrochemical energy. Transition metals, and their oxides, serve as a promising alternative to these precious metals. due to their intrinsic activity and sufficient stability in oxidative electrochemical environments. Among wide range of these metals, cobalt, manganese, nickel, and iron, have been extensively explored as bifunctional catalysts, capable of simultaneously catalyzing oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) for energy storage and conversion. Not only do they show innate electrochemical capabilities, but their structural diversity, as well as their ability to be mixed, doped, and combined with other materials such as graphene, make transition metal oxides a highly attractive subject in electrochemical and materials research. This review serves to summarize the research currently available concerning transition metal oxides, and their applications as a bifunctional catalyst for the utilized fuel cells and rechargeable metal-air batteris in alkaline media. Particularly, oxide synthesis and their structural properties are related to their electrochemical abilities, along with their behavior when introduced to other catalytic materials and dopants.